Association between PNPLA3 rs738409 polymorphism and nonalcoholic fatty liver disease (NAFLD) susceptibility and severity: A meta-analysis. Issue 7 (February 2019) - Dai, Guangrong; Liu, Pengfei; Li, Xiaomei; Zhou, Xiaoyan; He, Shuixiang
Abstract: Objective: This meta-analysis is to investigate the relationship between the patatin-like phospholipase domain containing 3 (PNPLA3) rs738409 polymorphism and the susceptibility and severity of nonalcoholic fatty liver disease (NAFLD). Methods: Chinese Journal Full-text Database, Wanfang Database, VIP Database, and PubMed Database were subjected to case-control study retrieving, from January 2008 to December 2014. Following key words were used: fatty liver, PNPLA3, and rs738409 gene or variants or polymorphism or alleles. Meta-analysis was performed based on the retrieved articles. Results: In total 65 studies were first retrieved according to the key words, and finally 21 studies with 14, 266 subjects were included. Meta-analysis showed that PNPLA3 rs738409 polymorphism exerted strong influence not only on fatty liver but also on the histological injury. PNPLA3 rs738409 [G] allele was a risk factor for NAFLD (GG vs CC, OR = 4.01, 95% CI 2.93–5.49; GC vs CC, OR = 1.88, 95% CI 1.58–2.24). PNPLA3 gene variant was significantly associated with the increased serum alanine aminotransferase (ALT) levels (GG vs CC, standardized mean difference  = 0.47, 95% CI 0.14–0.81). In addition, nonalcoholic steatohepatitis (NASH) was more frequently observed in G allele carriers (GG vs CC, OR = 3.24, 95% CI 2.79–3.76; GC vs CC, OR = 2.14, 95% CI 1.43–3.19). Conclusion: PNPLA3 rs738409 polymorphism is not only a factor significantly associated with the susceptibility of NAFLD, but also related to the susceptibility of aggressive diseases.